Preventing Foodborne Illness: Cyclosporiasis cayetanensis - Keith R. Schneider; Rachael Silverberg; Susie Richardson; Renée M. Goodrich-Schneider (EDIS)
Cyclospora cayetanensis is a microscopic, spore-forming, intestinal protozoan parasite and a known cause of the gastrointestinal infection cyclosporiasis, often referred to as “traveler’s diarrhea” for its prevalence among visitors to regions where the species is endemic. These organisms have a protective covering that makes them resistant to disinfectants and that gives Cyclospora the ability to survive outside of hosts for extended periods. The incidence of cyclosporiasis has been increasing worldwide, with several documented cases in the United States and Canada. This revised 4-page fact sheet was written by Keith R. Schneider, Rachael Silverberg, Susie Richardson, and Renée Goodrich Schneider, and published by the UF Department of Food Science and Human Nutrition, March 2015. (Photo: CDC/DPDx – Melanie Moser)